The selective grinding prosthetic feeding aid frequency influence towards premaxilla position on infant with complete unilateral cleft lip and palate - Lisda Damayanti Damayanti; Rasmi Rikmasari; Edy Machmud (Journal of Dentomaxillofacial Science, 2017)
Objective: The purpose of the research was to analyze the influence of selective grinding frequency towards premaxilla position of infant with complete unilateral cleft lip and palate using prosthetic feeding aid.Material and Methods: Ten infants with complete unilateral cleft lip and palate with wide alveolar cleft and rotating position of premaxilla were treated with prosthetic feeding aid. Impression was done twice to each subject before and after prosthetic feeding aid placement. The photograph was taken from each working model. Tracing was made on each photograph using photoQuad program on the assigned postulate spots. Adjustment towards the prosthetic feeding aid device was done every two week with selective grinding on the anatomical surface of acrylic on the palatolateral major and anteromedial minor defects, and relining with soft liner on the labial of anatomical surface was also done. Anatomical surface selective grinding was not exceeded 1–1.5 mm on every visit. The correlation analyze between selective grinding frequency of prosthetic feeding aid and premaxilla position used the Pearson correlation coefficient.Results: The correlation analysis between selective grinding prosthetic feeding aid frequency with premaxilla position on infant with complete unilateral cleft lip and palate have positive correlation with value of 23% or r = 0.479 and t-count = 1.544 or p-value = 0.1611.Conclusion: The more frequent the selective grinding on prosthetic feeding aid, the higher the premaxilla position change will increase towards midsagittal.